2006
DOI: 10.1111/j.1365-2516.2006.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in murine haemophilic synovitis: a quantitative grading system to assess blood‐induced synovitis

Abstract: Haemophilia is a congenital disorder that results in frequent bleeding into joints, in which a chronic and debilitating arthritis develops. The presence of blood evokes an inflammatory and proliferative synovial reaction. Although the molecular mechanisms and biochemical pathways which underlie this disorder are not known, significant advances have been made by studying a murine model of human haemophilic synovitis. In order to better understand and correlate the pathological, molecular and biochemical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 49 publications
0
65
1
Order By: Relevance
“…20; 180 The clinical, histopathologic, and radiologic changes initially described in hemophilia A mice by Valentino and colleagues are also seen in the hemophilia B mice. 180; 181 Importantly, these hemophilic changes are not seen in hemostatically normal mice.…”
Section: The Hemophilia B Mouse Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…20; 180 The clinical, histopathologic, and radiologic changes initially described in hemophilia A mice by Valentino and colleagues are also seen in the hemophilia B mice. 180; 181 Importantly, these hemophilic changes are not seen in hemostatically normal mice.…”
Section: The Hemophilia B Mouse Modelmentioning
confidence: 96%
“…Different parameters that are measured experimentally include: knee diameter, joint capsule bleeding score assessed by visual bleeding score, changes in body mass and histology using a grading scheme. 20; 21 Two different injury models were developed: one that induced a mechanical trauma to the joint and then required that the animals walk on a rotating rod apparatus and a second model induced hemarthrosis by puncture with a 30 gauge needle which was thought may mimic blood-induced arthropathy. 22 Using these models, recombinant hFVIII and human factor VIIa (hFVIIa) were evaluated for their ability to prevent acute joint bleeding in the hemophilia A mouse.…”
Section: The Hemophilia a Micementioning
confidence: 99%
“…27 Three or more independent reviewers blinded to the experimental conditions examined the entire joint space and articular surfaces of 2 adjacent sagittal sections from each knee. Areas of greatest synovial thickening and vascularity were identified, and 3 nonoverlapping fields from these regions were scored at high magnification and total synovitis scores from each knee averaged.…”
Section: Histologic Grading Of Synovitis Pathologymentioning
confidence: 99%
“…Ex vivo studies with canine cartilage suggest that a 4-d duration of blood exposure produces loss of cartilage matrix [7] . Experimental studies have also demonstrated that after a major hemarthrosis the joint cavity is filled with a dense inflammatory infiltrate, and the tissues become brown-stained due to hemosiderin deposition following the breakdown of erythrocytes [8,9] . Vascular hyperplasia takes place resulting in tenous and friable vessels prone to bleed creating a viscous cycle of bleedingvascular hyperplasia-bleeding.…”
Section: Pathogenesismentioning
confidence: 99%